Fabrication of Polyurethane–Polyacrylate Hybrid Latexes with High Organosilicon Content via Phase Inversion Emulsion Polymerization - Junhao Zhou; Furui Luo; Liming Tang; Zhaoxia Guo (Molecules)
Waterborne polyurethane, with a mechanical strength comparable to solvent-based types, is eco-friendly and safe, using water as a dispersion medium. Polyacrylate excels in film formation and weather resistance but suffers from “hot stickiness and cold brittleness”. Merging polyurethane and polyacrylate creates advanced hybrids, while organosilicon enhances properties but is restricted due to hydrolytic crosslinking. In this paper, a series of polyurethane–polyacrylate hybrid latexes with high organosilicon content were prepared using phase inversion emulsion polymerization technology. Even when the monomer content of 3-(methacryloyloxy)propyltrimethoxysilane (MPS) was increased to 10%, the polymerization process was stable, without the formation of a gel precipitate. The resulting latexes could remain stable for at least 6 months without significant changes in the properties of their films. The effects of MPS content on the mechanical and thermal properties of latex films were systematically researched. The study showed that with an increase in MPS dosage, the hardness and elastic modulus of the latex films increased, while the elongation at break and water absorption decreased, together with the increased glass transition temperature and surface hydrophilicity. This work aims to provide new theoretical guidance for the preparation of silicone-modified hybrid latexes, enabling their safe and stable production and storage.